A simple proof of Abel’s theorem on the lemniscate (2010)
Since Abel's original publication in 1827, his remarkable theorem on the constructibility of the division of the lemniscata has been demonstrated with the help of the theory of elliptic functions. The test given by Rosen in 1981 is considered, today, as definitive. It also uses the modern and intricate Class Field Theory. Here is a new, short and simple demonstration of Abel's theorem for the lemniscata along with its reciprocal. The only tools are the additive properties of the Gaussian lemniscological functions and some elements of Galois theory.